FROM THE HISTORY OF BUKHARA'S ARCHITECTURAL MONUMENTS OF THE IX-XII CENTURIES - Khamidova Muhabbat Samandarovna (Social science and innovation, 2023)
This article is dedicated to highlighting the peculiarities of architectural monuments built in Bukhara in the 9th-12th centuries. In it, the influence of scientific achievements during the first stage of the "Eastern Renaissance" on the architecture of the region, the continuation of historical traditions in national architecture, the innovations observed in the field, the peculiarities of architectural style and decorative art of Bukhara. studied on the example of famous architectural monuments